2022
DOI: 10.4266/acc.2022.01088
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis assessing the effectiveness of intravenous vitamin C in patients with sepsis and septic shock

Abstract: Sepsis continues to be leading cause of mortality among patients admitted to intensive care unit (ICU), with about 48.9 million cases of sepsis diagnosed and 11 million deaths worldwide in 2017 [1]. Despite significant advances in the understanding of the pathophysiology of sepsis, the mainstay management still relies on active fluid resuscitation for hemodynamic support, early administration of antibiotics, and identification of source and infection control [2]. Vitamin C has been suggested as a possible ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…A more recent meta-analysis reported that Vit C showed no evident clinical improvement and therefore effectiveness of the therapy was not recommended [59]. It is important to mention that in some studies, the basal levels of Vit C have been found to be below the reference value in patients with septic shock [60].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent meta-analysis reported that Vit C showed no evident clinical improvement and therefore effectiveness of the therapy was not recommended [59]. It is important to mention that in some studies, the basal levels of Vit C have been found to be below the reference value in patients with septic shock [60].…”
Section: Discussionmentioning
confidence: 99%